MALAIKAT DALAM PERPEKTIF HADIS: ANALISIS KOMPARATIF SYI’AH DAN SUNNI - Nurfi Etika Ningrum; Abdul Latif; Harrits Fadhillah Ahmad; Abdul Hakim; Muhammad Iqbal Rahman (Journal Khafi : Journal Of Islamic Studies, 2023)
This paper analyzes the role and function of angels in the perspective of hadithaccording to the two main schools of Islam, namely Shi'a and Sunni. The mainquestion raised is how the differences in the sources and methodologies of the hadithbetween the two schools affect their understanding of angels. In the Shi'a tradition,hadith is sourced not only from the Prophet Muhammad (peace be upon him) but alsofrom the ma'sham imams, who are considered to have the authority to convey religiousteachings. Meanwhile, in the Sunni tradition, the hadith emphasizes more on thenarration of the Prophet Muhammad (peace be upon him) and his companions. Thisstudy compares the views of the two schools on the role of angels in human life,including their duties such as recording deeds, delivering revelations, and interactingwith humans. This paper uses a descriptive method of analysis, using references fromthe main hadith books of the two sects, such as Al-Kafi by Al-Kulaini for Shi'ah andSahih al-Bukhari and Sahih Muslim for Sunni, this study provides a comprehensiveoverview of how both traditions view and respect the role of angels in Islamicteachings. In conclusion, despite differences in sources and methodologies, the twoschools agree on the importance of the role of angels in carrying out various tasksgiven by Allah Swt., reflecting the diversity of thought in Islam but still in one unity offaith.